Harvest season, productivity and physicochemical quality of peach fruits grown in Dois Vizinhos, Paraná State, Brazil - Nava, Gilmar Antonio; Kurschner, Eder Oneide; Paulus, Dalva (Semina: Ciências Agrárias, 2020)
The objective of this study was to determine the harvest time, main components of yield and the physicochemical quality attributes of peach cultivars produced in a subtropical climate. The study was carried out in the Fruit Growing sector of the Federal Technological University of Paraná, Campus Dois Vizinhos, Paraná State, Brazil. The main components of yield and estimated productivity, background color of the epidermis, pulp firmness, soluble solids (SS), titratable acidity (TA) and the SS/TA ratio of 17 peach cultivars were determined for two crop cycles: 2016 and 2017. The experimental design was a randomized block with four replicates of one tree per experimental unit, in a 17 x 2 bifactorial scheme (cultivars x years). Fruits of the cultivars: Aurora-1, Bonão, Douradão, Leonense, Ouromel, Rubimel and Zilli matured early, whereas those of Eldorado and BR-1 were last to mature. The cultivars Bonão, Charme and Eldorado were the most productive. Eldorado produced the highest caliber of fruits and Bonão produced the highest number of fruits per tree. The cultivars BR-1 and Eldorado produced the sweetest fruits and Leonense, the most acidic. The 2016 crop season provided greater productivity, with fruits of greater caliber and firmness of pulp.